Yuval N. Harari: Freedom blurred and demystified: (Part I) - Beorlegui, Carlos (Razón y fe, 2021)
Reading the texts of the influential writer Yuval Noha Harari produces a series of very opposing feelings that go from admiration to perplexity. Admiration for his great capacity for synthesis, very successful neologisms, the contribution of suggestive and accurate ideas, both with respect to the past and to our near future, etc. But, also, perplexity for the presence of numerous contradictions, which I am unable to elucidate if they are conscious and provocative, or just the expression of a different and confusing way of understanding the problems. This happens especially when the Israeli intellectual reflects on human freedom, one of his recurring themes, which is present in a special way in his latest works, as well as in his various interviews with the media.